Comparability and predictive ability of loan loss allowances: The role of accounting regulation versus bank supervision - Günther Gebhardt; Zoltán Novotny-Farkas (Goethe University Frankfurt, Center for Financial Studies (CFS), 2018)
We investigate whether and how the shift from discretionary forward-looking provisioning to the restrictive incurred loss approach under International Financial Reporting Standards (IFRS) in the European Union (EU) affects the cross-country comparability and predictive ability of loan loss allowances. Given bank supervisors' keen interest in comparable and adequate loan loss allowances, we also examine the role of supervisors in determining financial statement effects around IFRS adoption. We find that the application of the incurred loss approach has led to more comparable loan loss allowances. However, some differences persist in countries where supervisors were reluctant to enforce the incurred loss approach. Our results also suggest that the predictive ability of loan loss allowances improved following IFRS adoption. Finally, in supplemental analyses we document that increased comparability of loan loss allowances is associated with the cross-country convergence of the risk sensitivity of bank leverage indicating an improvement in the effectiveness of market discipline in the EU.
urn:nbn:de:hebis:30:3-437438
Keywords: M41; M48; G21; 330; comparability; loan loss allowances; IFRS; bank accounting; supervisory intervention